Franchising : an alternative business investment (a study based on eon franchise service dealer) / Anniza Mohd Hedzir - Mohd Hedzir, Anniza (1993)
Franchising has expanded rapidly around the world during the 1970s and 1980s. It is often viewed as an industry by itself. However, franchising is not an industry, but a process - an ongoing contractual relationship between a franchisor and a franchisee. Franchising is a distribution method which is being used by an increasing number of businesses for expansion and growth. Franchising is defined by the British Franchise Association as the method by which the owner of a business (franchisor) contractually agrees to allow another independent person or company (franchisee) to market a certain product or service within a specified geographical area